Daughter of the East : An Autobiography - Bhutto, Benazir 1953-2007 (London Pocket Book, 2008)
A timely new edition of the extraordinary life story of Pakistan's first woman Prime Minister -- now updated to assess recent developments in her country as it assumes a central role in world affairs.
Include Index and Illustrations
This ed. originally published: London: Simon & Schuster, 2007
Keywords: Politicians -- Prime ministers